Landslide Susceptibility Zonation Based on Seismic Vulnerability Index and Subsurface Lithology Derived from Resistivity Values - Ira Jam’iyatul Qalbiyah; Adi Susilo; Eko Andi Suryo (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to determine potential landslide-prone zones based on the seismic vulnerability index and subsurface lithology derived from electrical rock resistivity values. The research employs the microseismic method and the geoelectric resistivity method with a dipole–dipole configuration. Zones with high landslide susceptibility are identified at points exhibiting high values of the seismic vulnerability index. Based on data acquisition, the highest amplification factor was recorded at point D3 of 9.24, with a corresponding seismic vulnerability index of 24.57. Subsurface lithology analysis reveals an alluvium layer with a thickness of up to 25.00 meters overlying the bedrock. These datasets indicate that the alluvial soil is characterized by soft textures, incomplete consolidation, and low stability levels, rendering these specific points highly vulnerable to significant damage and landslide activity.